Changing trends in the disease burden of uterine cancer globally from 1990 to 2019 and its predicted level in 25 years - Song, Shuang; Zhang, Dandan; Wang, Yizi; Song, Zixuan (Frontiers in Oncology, 2024)
We aim to evaluate the global, regional, and national burden of Uterine Cancer (UC)from 1990 to 2019.We gathered UC data across 204 countries and regions for the period 1990-2019, utilizing the Global Burden of Disease Database (GBD) 2019 public dataset. Joinpoint regression analysis was employed to pinpoint the year of the most significant changes in global trends. To project the UC trajectory from 2020 to 2044, we applied the Nordpred analysis, extrapolating based on the average trend observed in the data.Furthermore, the Bayesian Age-Period-Cohort (BAPC) model with integrated nested Laplace approximations was implemented to confirm the stability of the Nordpred analysis predictions.Results: Globally, the age-standardized rate (ASR) of incidence for UC has increased from 1990 to 2019 with an Average Annual Percentage Change (AAPC) of 0.50 %.The ASR for death has declined within the same period (AAPC: -0.8%). An increase in the ASR of incidence was observed across all Socio -demographic Index (SDI) regions, particularly in High SDI regions (AAPC: 1.12 %), while the ASR for death decreased in all but the Low SDI regions. Over the past 30 years, the highest incidence rate was observed in individuals aged 55 -59 (AAPC: 0.76%). Among 204 countries and regions, there was an increase in the ASR of incidence in 165 countries and an increase in the ASR of deaths in 77 countries. Our projections suggest that both the incidence and death rates for UC are likely to continue their decline from 2020 to 2044.Conclusions: UC has significantly impacted global health negatively, with its influence stemming from a range of factors including geographical location, age -related and racial disparities, and SDI.